STRATEGY OF VILLAGE GOVERNMENT IN BUILDING RESILIENCE LOCAL ECONOMIC POTENTIALS IN BANJARHARJA VILLAGE KALIPUCANG DISTRICT PANGANDARAN - Juniawan, Ryan (Journal Education and Government Wiyata, 2023)
This research is motivated by the not yet optimal utilization of rural economic potential which is based on geographical advantages and local intellectual resources as an economic basis in rural development. This is evident from the low desire of the community to create their own jobs by utilizing regional potential, such as the manufacture of palm sugar or brown sugar, the limited availability of facilities and infrastructure to develop production activities and access to marketing, and the inadequate capacity of economic institutions or organizations in the community rural areas to develop modern ways of working accompanied by the use of appropriate technology.The research method used is descriptive method. This type of research is descriptive qualitative.Based on the results of research and discussion of Village Government Strategies in Building Local Economic Potential Resilience in Banjarharja Village, Kalipucang District, Pangandaran Regency, in general, it has been implemented in accordance with four strategic matters in realizing rural economic development based on potential, geographical and rural characteristics, however there are still some indicators whose implementation has not been optimal.The obstacles faced viz including the inadequate facilities to achieve the goal of managing village potential owned by the village government, the absence of collaboration by the village government with other parties, the absence of experts or resource persons guiding Banjarharja Village to create innovations for plantations that attract tourists, the not yet optimal government villages in identifying all village potentials to be developed and utilized due to the insufficient capacity of village officials and the low commitment of village officials to be able to manage village potentials.